Nitric acid modified fly ash-based SCR (selective catalytic reduction) catalyst as well as preparation method and application thereof

Through the fly ash-based SCR catalyst modified with nitric acid, the manganese and cerium bimetallic oxides are supported, the problem of the existing catalyst ineffective at low temperatures is solved, efficient catalytic reduction of nitrogen oxides is achieved, and good water resistance is provided, and it is suitable for NOX emission control in the non-electric industry.

CN119746848AActive Publication Date: 2025-04-04SHANDONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411968010.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing V2O5-WO3/TiO2 catalysts are effective at high temperatures, but are not suitable for catalytic reduction of low-temperature flue gas below 300℃, and cannot meet the strict NOX emission control needs of the non-power industry.

Method used

A fly ash-based SCR catalyst modified with nitric acid is used, which uses nitric acid modified fly ash as the support and is supported by manganese and cerium bimetallic oxides. The specific surface area and SiO2 ratio of fly ash are increased by nitric acid treatment, and selectively and efficiently catalytically reduce nitrogen oxides at low temperatures.

Benefits of technology

At 150°C, the NOX conversion rate reaches 100%, and remains above 90% within the range of 140 to 250°C. It has excellent water resistance and is suitable for practical industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746848A_ABST
    Figure CN119746848A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas-phase inorganic pollutant purification, and particularly provides a nitric acid modified fly ash-based SCR catalyst which takes nitric acid modified fly ash as a carrier and is loaded with manganese and cerium bimetal oxides. Through nitric acid treatment, the specific surface area of the fly ash can be increased, the average pore size can be reduced, the proportion of SiO2 in the fly ash can be effectively increased, some impurities are removed, and loading of active metal is facilitated. After the catalyst is loaded with a manganese and cerium bimetallic oxide, nitrogen oxide can be selectively and efficiently catalytically reduced at a low temperature, and the NOX conversion rate reaches 100% at 150 DEG C and is kept at 90% or above within the range of 140-250 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas-phase inorganic pollutant purification, and in particular to a nitric acid-modified fly ash-based SCR catalyst, a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, nitrogen oxides (NO X ) has become one of the main pollutants leading to atmospheric pollution problems and is also one of the important causes of haze, acid rain and photochemical smog. The increase in NOx emissions will pose a huge threat to the environment and human health.

[0004] Selective catalytic reduction of NO with NH3 X (NH3-SCR) technology has been used in NO X V2O5-WO3 / TiO2 catalyst is widely used in the field of emission reduction. V2O5-WO3 / TiO2 catalyst is widely used commercially due to its excellent SCR activity, thermal stability and anti-poisoning ability to SO2. However, V2O5-WO3 / TiO2 catalyst is used for catalytic reduction of flue gas at high temperature and is not suitable for catalytic reduction of low-temperature flue gas below 300℃. At present, NO in non-power industries including steel, cement, glass, etc. X Emission control is also relatively strict. Since the flue gas temperature of the above non-power industries is usually below 300°C, commercial V2O5-WO3 / TiO2 catalysts are not applicable. The development of vanadium-free catalysts with low-temperature SCR activity is urgently needed by non-power industries.

[0005] Fly ash is a product of coal-fired boiler combustion. It is spherical in appearance, smooth in surface and porous in structure. Its main components are SiO2, Al2O3, Fe2O3 and MgO, etc. It is alkaline. If fly ash is not handled properly, it will generate dust, pollute the air and water quality, and harm human health. As a porous material, fly ash has good adsorption capacity and can be used as an adsorbent and catalyst carrier. Summary of the invention

[0006] In order to overcome the above problems, the present invention provides a nitric acid-modified fly ash-based SCR catalyst and a preparation method and application thereof.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a nitric acid-modified fly ash-based SCR catalyst, which uses nitric acid-modified fly ash as a carrier and is loaded with manganese and cerium bimetallic oxides.

[0009] The second aspect of the present invention provides a method for preparing the fly ash-based SCR catalyst modified by nitric acid according to the first aspect, comprising the following steps:

[0010] (1) soaking the dried fly ash in a nitric acid solution, washing it to neutrality, and drying it to obtain nitric acid-modified fly ash;

[0011] (2) adding fly ash modified by nitric acid to a mixed solution of manganese salt and cerium salt, heating and stirring until water evaporates, and drying to obtain an intermediate;

[0012] (3) The intermediate is aerobically calcined to obtain a nitric acid-modified fly ash-based SCR catalyst.

[0013] The third aspect of the present invention provides the fly ash-based SCR catalyst modified by nitric acid as described in the first aspect for use in the selective catalytic reduction of nitrogen oxides at low temperature.

[0014] The beneficial effects of the present invention are:

[0015] (1) The present invention provides a nitric acid-modified fly ash-based SCR catalyst, which uses nitric acid-modified fly ash as a carrier and is loaded with manganese and cerium bimetallic oxides. The nitric acid treatment can not only increase the specific surface area of ​​the fly ash and reduce the average pore size, but also effectively increase the proportion of SiO2 in the fly ash, while removing some impurities, which is beneficial to the loading of active metals. After loading manganese and cerium bimetallic oxides, nitrogen oxides can be selectively and efficiently catalytically reduced at low temperatures. At 150°C, NO X The conversion rate reaches 100% and remains above 90% in the range of 140-250°C.

[0016] (2) The fly ash-based SCR catalyst modified by nitric acid provided by the present invention has excellent water resistance. Under 5% water vapor conditions, the NO X The conversion rate only dropped by about 5% and remained stable for 6 hours. X The conversion rate was restored to 100%. This indicates that the fly ash-based SCR catalyst modified by nitric acid is suitable for practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 XRD images of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Ce / AFA modified by nitric acid prepared in Comparative Example 2, and the original fly ash (FA);

[0019] Figure 2 is the XPS spectrum of Mn2p;

[0020] Figure 3 is the spectrum of Ce 3d XPS;

[0021] Figure 4 This is the system used in the fixed bed denitrification reaction experiment;

[0022] Figure 5 The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Mn-Fe / AFA modified by nitric acid prepared in Comparative Example 3, and the fly ash-based catalyst Fe-Mn-Ce / AFA modified by nitric acid prepared in Comparative Example 4 at 125-250°C;

[0023] Figure 6 The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1 and the catalyst Mn-Ce / Ti prepared in Comparative Example 5 at 125-250°C;

[0024] Figure 7 The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Mn-Fe / AFA modified by nitric acid prepared in Comparative Example 3, the fly ash-based catalyst Fe-Mn-Ce / AFA modified by nitric acid prepared in Comparative Example 4, and the catalyst Mn-Ce / Ti prepared in Comparative Example 5 at 125°C;

[0025] Figure 8 The water resistance results of the nitric acid-modified fly ash-based SCR catalyst Mn—Ce / AFA prepared in Example 1. DETAILED DESCRIPTION

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0028] A first typical embodiment of the present invention provides a nitric acid-modified fly ash-based SCR catalyst, which uses nitric acid-modified fly ash as a carrier and is loaded with manganese and cerium bimetallic oxides.

[0029] In one or more embodiments, in the nitric acid-modified fly ash-based SCR catalyst, the loading amounts (mass ratio) of manganese and cerium are both 4-6%, preferably 5%.

[0030] A second typical embodiment of the present invention provides a method for preparing the fly ash-based SCR catalyst modified by nitric acid according to the first aspect, comprising the following steps:

[0031] (1) soaking the dried fly ash in a nitric acid solution, washing it to neutrality, and drying it to obtain nitric acid-modified fly ash;

[0032] (2) adding fly ash modified by nitric acid to a mixed solution of manganese salt and cerium salt, heating and stirring until water evaporates, and drying to obtain an intermediate;

[0033] (3) The intermediate is aerobically calcined to obtain a nitric acid-modified fly ash-based SCR catalyst.

[0034] In one or more embodiments, in step (1), the particle size of the fly ash is 150-300 mesh, preferably 200 mesh.

[0035] In one or more embodiments, in step (1), the concentration of the nitric acid solution is 4 to 6 mol / L, preferably 5 mol / L.

[0036] In one or more embodiments, in step (1), the soaking temperature is 80-100° C., preferably 90° C.; and the soaking time is 0.5-2 h, preferably 1 h.

[0037] In one or more embodiments, in step (2), the manganese salt is selected from one or more of manganese nitrate, manganese chloride, manganese sulfate or manganese acetate.

[0038] In one or more embodiments, in step (2), the cerium salt is selected from one or more of cerium chloride, cerium nitrate, cerium acetate, and ammonium cerium nitrate, preferably cerium nitrate.

[0039] In one or more embodiments, in step (2), the heating temperature is 55-70°C, preferably 60°C.

[0040] In one or more embodiments, in step (3), the calcination temperature is 450-600° C., preferably 60° C.; the calcination time is 2.5-4 h, preferably 3 h.

[0041] A third typical embodiment of the present invention provides the fly ash-based SCR catalyst modified by nitric acid as described in the first aspect for use in the selective catalytic reduction of nitrogen oxides at low temperature.

[0042] In one or more embodiments, the temperature for the selective catalytic reduction of nitrogen oxides is 140-250°C, preferably 150°C.

[0043] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0044] Example 1

[0045] The fly ash raw material obtained from a coal-fired power plant of Huaneng Group was ground to 200 mesh and dried overnight in a drying oven at 105°C. The dried fly ash was named FA. Subsequently, the dried fly ash was soaked in a nitric acid (5 mol / L) solution and treated in a water bath at 90°C for 1 hour. The mixed solution of nitric acid and FA was then filtered and washed with deionized water until the solution was neutral. Then FA was dried in a drying oven at 105°C until the water was completely evaporated to obtain the intermediate AFA.

[0046] A certain amount of manganese nitrate solution and cerium nitrate hexahydrate (Ce(NO3)3·6H2O) were added to deionized water and mixed thoroughly to form a precursor solution. The intermediate AFA was then added directly to the precursor solution, heated in a 60°C water bath, and stirred until the water evaporated. The obtained sample was dried in a drying oven at 105°C overnight, and the sample was taken out of the drying oven and calcined in a muffle furnace in an air atmosphere of 500°C for 3 hours. Finally, the calcined material was naturally cooled to room temperature to obtain a nitric acid-modified fly ash-based SCR catalyst Mn-Ce / AFA. The loading amount (mass ratio) of manganese and cerium in the nitric acid-modified fly ash-based SCR catalyst Mn-Ce / AFA is 5%.

[0047] Comparative Example 1

[0048] Add a certain amount of manganese nitrate solution to deionized water and mix thoroughly to use as a precursor solution. Then add the intermediate AFA prepared in Example 1 directly to the precursor solution, heat in a 60°C water bath, and stir until the water evaporates. The obtained sample is dried in a drying oven at 105°C overnight, and the sample is taken out of the drying oven and calcined in a muffle furnace in an air atmosphere of 500°C for 3 hours. Finally, the calcined material is naturally cooled to room temperature to obtain a nitric acid-modified fly ash-based catalyst Mn / AFA. The manganese loading (mass ratio) in the nitric acid-modified fly ash-based catalyst Mn / AFA is 5%.

[0049] Comparative Example 2

[0050] Add a certain amount of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) to deionized water and mix thoroughly to use as a precursor solution. Then add the intermediate AFA directly to the precursor solution, heat it in a 60°C water bath, and stir until the water evaporates. The obtained sample is dried in a drying oven at 105°C overnight, and the sample is taken out of the drying oven and calcined in a muffle furnace in an air atmosphere at 500°C for 3 hours. Finally, the calcined material is naturally cooled to room temperature to obtain a nitric acid-modified fly ash-based catalyst Ce / AFA. The cerium loading (mass ratio) in the nitric acid-modified fly ash-based catalyst Ce / AFA is 5%.

[0051] Comparative Example 3

[0052] Add a certain amount of manganese nitrate solution and ferric nitrate to deionized water and mix thoroughly to use as a precursor solution. Then add the intermediate AFA directly to the precursor solution, heat it in a 60°C water bath, and stir until the water evaporates. The obtained sample is dried in a drying oven at 105°C overnight, and the sample is taken out of the drying oven and calcined in a muffle furnace in an air atmosphere of 500°C for 3 hours. Finally, the calcined material is naturally cooled to room temperature to obtain a nitric acid-modified fly ash-based catalyst Mn-Fe / AFA. The loading amount (mass ratio) of manganese and iron in the nitric acid-modified fly ash-based catalyst Mn-Fe / AFA is 5%.

[0053] Comparative Example 4

[0054] A certain amount of manganese nitrate solution, cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and ferric nitrate were added to deionized water and mixed thoroughly to form a precursor solution. The intermediate AFA was then added directly to the precursor solution, heated in a 60°C water bath, and stirred until the water evaporated. The obtained sample was dried in a drying oven at 105°C overnight, and the sample was taken out of the drying oven and calcined in a muffle furnace in an air atmosphere of 500°C for 3 hours. Finally, the calcined material was naturally cooled to room temperature to obtain a nitric acid-modified fly ash-based catalyst Fe-Mn-Ce / AFA. The loading amount (mass ratio) of manganese, cerium and iron in the nitric acid-modified fly ash-based catalyst Fe-Mn-Ce / AFA is 5%.

[0055] Comparative Example 5

[0056] Add a certain amount of manganese nitrate solution and cerium nitrate hexahydrate (Ce(NO3)3·6H2O) to deionized water and mix thoroughly to use as a precursor solution. Then add TiO2 (specific particle size is 200 mesh) directly to the precursor solution, heat in a 60°C water bath, and stir until the water evaporates. The obtained sample is dried in a drying oven at 105°C overnight, and the sample is taken out of the drying oven and calcined in a muffle furnace in an air atmosphere at 500°C for 3 hours. Finally, the calcined material is naturally cooled to room temperature to obtain the catalyst Mn-Ce / Ti. The loading amount (mass ratio) of manganese and cerium in the catalyst Mn-Ce / Ti is 5%.

[0057] Example 2

[0058] Table 1 shows the proportion of each component of the original fly ash (FA) and the fly ash modified by nitric acid, i.e., the intermediate (AFA). As can be seen from Table 1, nitric acid treatment can effectively increase the proportion of SiO2 in fly ash and remove some impurities, which is beneficial to the loading of active metals.

[0059] Table 1 Proportion of each component of original fly ash (FA) and intermediate (AFA)

[0060]

[0061] Example 3

[0062] 3.1 Table 2 shows the physical structures of the original fly ash (FA), the fly ash modified by nitric acid, i.e., the intermediate (AFA), and the catalysts prepared in Comparative Examples 1 to 4. Compared with FA, the specific surface area of ​​AFA after nitric acid treatment increased from 0.64 m 2 / g increased to 25.50m 2 / g, indicating that acid modification will produce more pores in fly ash, increase the specific surface area of ​​fly ash, and make the active components evenly loaded, thereby improving the activity of the catalyst.

[0063] Table 2 Physical structures of original fly ash (FA), intermediate (AFA) and catalysts prepared in Comparative Examples 1 to 4

[0064]

[0065] 3.2 Figure 1 The XRD images of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Ce / AFA modified by nitric acid prepared in Comparative Example 2, and the original fly ash (FA) are shown in FIG. Figure 1It can be seen that the main diffraction peaks of all samples are the characteristics of fly ash carrier, that is, the crystalline phases of quartz and mullite, which are consistent with the standard PDF card. The diffraction pattern of Ce / AFA shows a cubic fluorite-type CeO2 diffraction peak, indicating that CeO2 has poor dispersion and high crystallinity, and mainly exists on the catalyst surface in the form of crystals. For the Mn-Ce / AFA catalyst, XRD cannot detect MnO X The interaction between manganese and cerium in manganese and cerium bimetallic oxides can promote the transformation of active components in the catalyst from the crystalline phase to the amorphous phase, forming Mn-Ce active sites, thereby improving the low-temperature catalytic performance.

[0066] Example 4

[0067] Figure 2 The XPS spectrum of Mn2p is shown. 4+ The proportion of Mn is 32.24%. 4+ The presence of Mn is beneficial to accelerate the oxidation of NO to NO2 and promote the "fast SCR" reaction, thereby improving the catalytic performance of the catalyst at low temperatures. 4+ and Mn 3+ The presence of can also provide more acidic sites, promoting the adsorption and activation of gas molecules, thereby improving the catalytic performance.

[0068] Figure 3 The XPS spectrum of Ce 3d is shown. The spectrum of Ce 3d is fitted to eight peaks labeled u, u', u", u'', v, v', v", v'', which belong to Ce 33 d / 3 and Ce 3d 5 / 2 The peaks labeled v' and u' belong to Ce 3+ , the other peaks belong to Ce 4+ . Ce in Mn-Ce / AFA catalyst 3+ The proportion of Ce is 19.31%. 3+ It will lead to charge imbalance, produce more oxygen vacancies and unsaturated chemical bonds, enhance the mobility of oxygen on the catalyst surface, make oxygen easier to adsorb, and promote the low-temperature denitrification performance of the catalyst.

[0069] From the above results, it can be known that the manganese and cerium bimetallic oxide prepared in Example 1 is a mixed oxide composed of multiple oxides. The valence of manganese is +4, +3 and +2; the valence of cerium is +3 and +4.

[0070] Experimental Example 1

[0071] Figure 4This is the system used in the fixed bed denitrification reaction experiment. The experimental process is: premix the gases in proportion to prepare simulated flue gas, the simulated flue gas enters the fixed bed quartz reactor (filled with 0.1g of the prepared catalyst) for catalytic denitrification, and the gas composition is analyzed by a flue gas analyzer.

[0072] The reaction conditions of the experimental process are as follows: the simulated flue gas flow rate is 100 mL min -1 . [NO X ]=[NH3]=500ppm([NO X ]=[NO]+[NO2]), [O2]=5vol%, [H2O]=5vol%, N2 is the balance gas, the gas mass space velocity (WHSV) is 60,000mL / (g·h), and the temperature range of the catalytic test is 75-250℃.

[0073] Figure 5 The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Mn-Fe / AFA modified by nitric acid prepared in Comparative Example 3, and the fly ash-based catalyst Fe-Mn-Ce / AFA modified by nitric acid prepared in Comparative Example 4 at 125-250°C is shown in FIG. Figure 5 It can be seen that loading various metals can improve the NO of the catalyst to a certain extent. X The conversion rate is significantly improved when Mn and Ce are loaded on AFA. The denitration performance of Mn-Ce / AFA is better than other catalysts. The NOX conversion rate reaches 100% at 150°C and remains above 90% in the range of 140-250°C.

[0074] Figure 6 The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1 and the catalyst Mn-Ce / Ti prepared in Comparative Example 5 at 125-250°C is as follows: Figure 6 It can be seen that the catalytic performance of Mn-Ce / AFA is better than that of Mn-Ce / Ti catalyst, indicating that the fly ash-based catalyst prepared by the present invention can effectively improve the activity, and the effect is no less than that of other catalysts.

[0075] Figure 7The catalytic performance of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1, the fly ash-based catalyst Mn / AFA modified by nitric acid prepared in Comparative Example 1, the fly ash-based catalyst Mn-Fe / AFA modified by nitric acid prepared in Comparative Example 3, the fly ash-based catalyst Fe-Mn-Ce / AFA modified by nitric acid prepared in Comparative Example 4, and the catalyst Mn-Ce / Ti prepared in Comparative Example 5 at 125°C. As the temperature rises, the average energy of the reactant molecules increases, thereby increasing the collision frequency and collision energy of the reactant molecules, thereby accelerating the reaction rate. Testing at low temperatures helps to eliminate the effects of diffusion, thereby more accurately studying the intrinsic kinetics of the reaction, so the lowest temperature within the measurement temperature range was selected. Figure 7 It can be seen that at 125 °C, the reaction rate of the Mn-Ce / AFA catalyst is the fastest.

[0076] Figure 8 The water resistance results of the fly ash-based SCR catalyst Mn-Ce / AFA modified by nitric acid prepared in Example 1 are as follows: Figure 8 It can be seen that under 5% water vapor conditions, the NO X The conversion rate only dropped by about 5% and remained stable for 6 hours. X The conversion rate was restored to 100%. This indicates that the fly ash-based SCR catalyst modified by nitric acid is suitable for practical industrial applications.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A fly ash-based SCR catalyst modified by nitric acid, characterized in that: The fly ash modified by nitric acid is used as a carrier and loaded with bimetallic oxides of manganese and cerium.

2. The nitric acid-modified fly ash-based SCR catalyst according to claim 1, characterized in that: In the nitric acid-modified fly ash-based SCR catalyst, the loading amounts (mass ratio) of manganese and cerium are both 4-6%, preferably 5%.

3. The method for preparing the fly ash-based SCR catalyst modified by nitric acid according to claim 1 or 2, characterized in that: The following steps are involved: (1) soaking the dried fly ash in a nitric acid solution, washing it to neutrality, and drying it to obtain nitric acid-modified fly ash; (2) adding fly ash modified by nitric acid to a mixed solution of manganese salt and cerium salt, heating and stirring until water evaporates, and drying to obtain an intermediate; (3) The intermediate is aerobically calcined to obtain a nitric acid-modified fly ash-based SCR catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the particle size of fly ash is 150-300 mesh, preferably 200 mesh; Alternatively, in step (1), the concentration of the nitric acid solution is 4 to 6 mol / L, preferably 5 mol / L.

5. The preparation method according to claim 3, characterized in that: In step (1), the soaking temperature is 80-100° C., preferably 90° C.; the soaking time is 0.5-2 h, preferably 1 h.

6. The preparation method according to claim 3, characterized in that: In step (2), the manganese salt is selected from one or more of manganese nitrate, manganese chloride, manganese sulfate or manganese acetate; Or, in step (2), the cerium salt is selected from one or more of cerium chloride, cerium nitrate, cerium acetate, and ammonium cerium nitrate, preferably cerium nitrate.

7. The preparation method according to claim 3, characterized in that: In step (2), the heating temperature is 55-70°C, preferably 60°C.

8. The preparation method according to claim 3, characterized in that: In step (3), the calcination temperature is 450-600° C., preferably 60° C.; the calcination time is 2.5-4 h, preferably 3 h.

9. The fly ash-based SCR catalyst modified by nitric acid according to claim 1 or 2 is used for selective catalytic reduction of nitrogen oxides at low temperature.

10. The use according to claim 10, characterized in that The temperature for the selective catalytic reduction of nitrogen oxides is 140-250°C, preferably 150°C.

Citation Information

Patent Citations

  • Method for preparing titanium dioxide photocatalyst carried by nitric-acid-modified coal ash serving as carrier

    CN102698786A

  • Preparation method of modified fly ash supporting manganese and cerium dual-metal denitration catalyst

    CN106238040A

  • Manganese-based low-temperature flue gas denitration catalyst and preparation method thereof

    CN109569587A

  • Catalyst capable of simultaneously removing CO, SO2 and NOx

    CN111715234A

  • Low-temperature desulfurization and denitration catalyst and preparation method thereof

    CN111822009A